A Golgi apparatus‑related subtype and risk signature predicts prognosis and evaluates immunotherapy response in gastric cancer - Ruyue Chen; Zengwu Yao; Lixin Jiang; Jinchen Hu (Discover Oncology)
Abstract Background Gastric cancer (GC) remains a significant health burden, calling for the discovery of novel biomarkers. Golgi apparatus, a crucial cellular organelle involved in tumorigenesis, remains underexplored in GC research. A comprehensive understanding of its role and associated mechanisms is urgently needed. Materials and methods Utilizing the TCGA-STAD dataset as the training cohort and GSE84433 as the validation cohort, we explored potential associations between Golgi apparatus-related genes (GARG) and GC clinical risk. We aimed to decipher the prognostic significance and underlying biological mechanisms of these genes via consistent clustering, differential expression analysis, enrichment analyses, and immune infiltration profiling. To assess the relationship between risk stratification and survival outcomes, drug sensitivity, and immune infiltration, we developed the Golgi Apparatus-Related Risk Signature (GARRS). The reliability of GARRS was further corroborated using immunohistochemical staining. Results Consensus clustering based on 17 GARG identified two patient subgroups, C1 and C2, exhibiting differential survival, immune scores, and immune cell infiltration. We developed a GARRS using Cox-Lasso regression analysis, accurately stratifying patients into high- and low-risk groups. GARRS’ validity was confirmed in the validation set and immunohistochemical staining. Our findings underline the Golgi apparatus' significance in the GC immune microenvironment and GARRS' utility in predicting GC survival outcomes. Conclusion This study underscores the association between Golgi apparatus subtypes and GC immunotumor microenvironment. GARRS, validated for its prognostic, immune infiltration, and drug sensitivity predictive abilities, offers new insights into gastric cancer treatment strategies.